SISTEM INFORMASI BERBASIS WEB SEBAGAI ALAT KORDINATOR POSKO TANGGAP DARURAT BANTUAN BENCANA - , Agus Sehatman Saragih ([Yogyakarta] : Universitas Gadjah Mada, 2012)
shelter Deficit information regarding the needs of resourceâs type and amount and the location of emergency- are factors that inhibit aid distribution processes. Inadequate coordination system between disasters handling performer severs the less optimal aid resources distribution. Aid multiplication and deposits frequently take places in one emergency-shelter. shelter In disaster emergency situation a tools or coordination will be strongly required. Web-based information system as a coordinator tools is expected able to accelerate information proliferation send by emergency- to central shelter and donor. In addition, coordination information system is expected serves as reference in optimizing aid resources distribution. Coordination information system facilitates the administration for estimates the list of requirement ad stock, presents graphic (total refugee, stock and aid requirement), providing reception and distribution transaction reports in form excel file (.xls). However, it requires further development in determines minimum level of aid stock with high need rates.